Utility of PREDICT-HF score in high-risk Asian heart failure patients receiving sacubitril/valsartan - Hsu, Chien-Yi; Chang, Hung-Yu; Chao, Chieh-Ju; Chiou, Wei-Ru; Lin, Po-Lin; Chung, Fa-Po; Lin, Wen-Yu; Huang, Jin-Long; Liang, Huai-Wen; Liao, Chia-Te; Lee, Ying-Hsiang (Frontiers in Cardiovascular Medicine, 2022)
Objective: The aim of this study was to investigate the application of sacubitril/valsartan in clinical practice and the utility of PREDICT-HF score for outcome prediction in Asian heart failure patients with difference risk profiles. Methods: The TAROT-HF study was a multicenter, single-arm, observational study. Totally 1,187 outpatients with HFrEF treated with sacubitril/valsartan were enrolled and categorized by: (1) high-risk group with ≥1 of the following three risk factors: old age (≥80 years), low baseline systolic blood pressure (<100mmHg), and renal impairment (eGFR <30ml/min/1.73 m2), and (2) standard-risk group, those who did not have any risk factors. Clinical outcomes were assessed using the PREDICT-HF risk model. Results: A total of 305 (25.7%) patients matched the criteria for the high-risk group. The event rates of cardiovascular death or first unplanned heart failure hospitalization (HFH) among the overall population, high-risk, and standard-risk groups were 13.7, 24.9, and 10.8 events per 100 patient-years, respectively. The C statistics for the PREDICT-HF model in the overall cohort and high-risk group for cardiovascular death or first unplanned HFH at 2 years were 0.73 (95% CI 0.70-0.76) and 0.71 (95% CI 0.65-0.76), respectively. The permanent discontinuation rate among the high-risk patients was significantly higher than that among the standard-risk patients (8.3 versus 2.5 per 100 patient-years, p<0.001). Conclusions: Real-world outcomes of the TAROT-HF study demonstrated that the PREDICT-HF model performed well in Asian HFrEF patients. Three easily detected clinical profiles of age, renal function, and systolic BP could help to identify patients at risk before initiating sacubitril/valsartan.